Frequency of second mesiobuccal canal in permanent maxillary first molars using the operating microscope and selective dentin removal: A clinical study - Suroopa Das; Manjusha M Warhadpande; Saurabh A Redij; N G Jibhkate; Husain Sabir (Wolters Kluwer Medknow Publications, 2015)
Purpose: The aim of this study was to investigate whether the combination of operating microscope and selective dentin removal increased the frequency of second mesiobuccal (MB2) canal detection in permanent maxillary first molar teeth. Materials and Methods: One hundred fifty permanent maxillary first molars indicated for root canal treatment were randomly selected from patients belonging to the age group of 18-45 years irrespective of gender. After access cavity preparation and location of main canals, the MB2 canal orifice was sought in all teeth with an endodontic explorer under direct vision (Stage I), then under magnification with the aid of operating microscope (Stage II) and finally with the combined use of operating microscope and selective dentin removal (Stage III). Results: MB2 canals were detected in 36%, 54% and 72% of the teeth in Stages I-III, respectively. Conclusion: This study demonstrated that dental operating microscope when used along with adjunctive aids such as selective dentin removal/troughing and good clinical knowledge will increase the ability of dental clinician to locate MB2 canals.